Change in smoking cessation stage over 1 year in patients with schizophrenia: a follow up study in Japan - Yuji Higuchi; Masaki Fujiwara; Naoki Nakaya; Maiko Fujimori; Chinatsu Hayashibara; Ryuhei So; Ikuta Shinkawa; Kojiro Sato; Yuji Yada; Masafumi Kodama; Hiroshi Takenaka; Yoshiki Kishi; et al. (BMC Psychiatry, 2019)
Abstract Background We performed a follow up study about willingness and behaviors to quit smoking among smokers with schizophrenia in Japan. Methods Participants were outpatients with schizophrenia aged 20–69 years who had been visiting the hospital for ≥1 year as of April 1, 2016, and had visited the hospital more than once in the previous 6 months. A baseline survey on smoking behaviors including current smoking status and smoking cessation stage, was administered in 420 participants that were randomly extracted from a patient pool (n = 680) in 2016, and a follow-up survey was administered in 2017. We calculated the distribution and change in smoking cessation stage, number of smokers and nonsmokers after 1 year, and quitting rate from a naturalistic 1-year smoking-cessation follow up. Results The number of baseline respondents was 350; 113 current smokers and 68 former smokers. Among the 113 current smokers, 104 (92.0%) were followed for 1 year, 79 (70.0%) were interested in smoking cessation, and only 7 had received smoking cessation treatments at baseline. Among the tracked 104 participants, only 6 (5.8%) stopped smoking after 1 year. Among the 25 participants who had intentions to quit smoking within 6 months at baseline, 6 (24.0%) maintained their intention to quit smoking for 1 year, and 16 (64.0%) did not maintain their intention to quit smoking. Conclusions Our findings showed that many smokers with schizophrenia were interested in quitting smoking, but few patients received treatment and actually quit smoking. Timely intervention, including the option to receive smoking cessation treatment, is necessary for those patients with schizophrenia who smoke. Trial registration UMIN Clinical Trials Registry (UMIN000023874, registered on August 31, 2016).